Quantification of Organic Solvent Concentration Profiles in Ion Exchange Membranes Via Confocal Raman Microscopy - Götz, Carina; Komma, Miriam; Dworschak, Dominik; Thiele, Simon; Böhm, Thomas (Advanced Materials Interfaces, 2023)
The perfluorinated sulfonic acid membranes used in direct alcohol fuel cells cause low faradaic efficiency and performance due to alcohol absorption and permeation. Thus, a measurement setup is sought that enables a direct evaluation of the suitability of polymer electrolytes for this application. A 3D-printed diffusion cell setup capable of measuring the interaction between the organic solvents, such as alcohols, and a proton exchange membrane via confocal Raman microscopy is introduced. The cell design employs flow channels to mimic the flow fields of electrochemical cell tests. Exemplarily, information on the interaction of membranes like Nafion 212 and the composite membrane Nafion XL with 1 m solutions of organic solvents such as 2-propanol, acetone, and ethanol are provided to demonstrate the applicability of this setup. The Raman diffusion cell is capable of quantifying the preferred solvent uptake, which is characterized by the sorption coefficient, the permeability, and the concentration gradient within the membrane. These properties can be obtained in situ and in a time-resolved manner. Thus, this diffusion cell setup is a powerful and accessible tool for screening membrane compatibility with various liquids.
CRIS-Team Scopus Importer:2023-12-15
Keywords: fuel cells; nafion; organic solvents; PEMFC; permeability; raman; swelling